Study protocol for a randomized controlled trial evaluating the effectiveness of a mother-child intervention model of neurogenic tremor as an add-on to treatment for emotional disorders in adolescents - Yanli Zhao; Jiahua Xu; Jie Zhang; Jiaqi Song; Ning Yang; Hongzhen Fan; Zhe Dong; Shuping Tan (BMC Complementary Medicine and Therapies)
Abstract Background Adolescents exhibit a high prevalence of mental health disorders, with more than half of all cases emerging before the age of 14 years. Since the advent of the COVID-19 pandemic, there has been a marked upsurge in anxiety and depression among adolescents across several nations. Emotional disorders often lead to severe outcomes, including school absenteeism, self-harm, and suicidal tendencies. The suboptimal efficacy of pharmacotherapy, compounded by limited availability and substantial costs associated with individual psychotherapy, underscores the critical need for identifying simple yet efficacious psychotherapeutic interventions suitable for both individual and group settings. Tension and Trauma Release Exercise (TRE) is a mind-body therapeutic approach that efficiently alleviates symptoms of anxiety and depression. This randomized controlled trial (RCT) aims to evaluate the effectiveness of a mother-child intervention model using TRE in enhancing the clinical management of adolescent patients diagnosed with emotional disorders. Methods This study recruits 140 dyads of adolescents with emotional disorders and their mothers, randomly assigned to intervention or control groups. The intervention arm combines eight weeks of standard pharmacotherapy with an eight-week TRE group therapy, assessing at baseline, post-8-week treatment, and three-month follow-up. Initially, controls receive eight weeks of standard medication with parallel assessments, later transitioning to the same TRE intervention while maintaining continuous evaluation. The study further examines the influence of maternal emotional health on adolescent treatment response and investigates associated neurophysiological and psychological mechanisms. Discussion This research endeavors to identify a straightforward and potent body-oriented psychological intervention that could improve the clinical outcomes for adolescent patients with emotional disorders. Such findings would carry profound implications not only for the healthy development of teenagers but also for potentially mitigating the burden on families, educational institutions, and society as a whole. Trial registration ChiCTR2100044553, Registered March 24, 2021.